THE INSERTION OF SOFT SKILL ON STUDENTS’ SPEAKING SKILL AT THE THIRD SEMESTER OF TBI DEPARTMENT AT STAIN PAMEKASAN - Handayani, Titik; Rabbianty, Eva Nikmatul (Institut Agama Islam Negeri Madura, 2020)
Many students get difficulties in speaking English because of a weak soft skill they have, such as motivation, creativity, and self-confidence. Therefore, lecturers? role in inserting soft skill in teaching speaking is essential because learning success is influenced more by soft skill than Intellectual Quotient. This study discussed kinds of soft skills inserted by lecturers in teaching speaking, the ways of lecturers insert them, and how those soft skills help students speak English. This study used qualitative approach by descriptive research design. The data are obtained from English lecturers and TBI students at the third semester of STAIN Pamekasan, period 2014/2015 by observation, field note, interview, and documentation. The results revealed that there are kinds of soft skills inserted by the lecturers, such as self-perceptions, motivation, perseverance, metacognition, social skill, and creativity. Whereas, the ways lecturers insert them are by using classroom discussion, reward, telling story, teacher talk, ordering students to perform drama, microteaching, asking students to use name tag, and sometimes lecturers use the same way in the next meeting if the previous materials have not finished. Those soft skills contribute to the students? speaking skill, such as making them more communicative, more interactive, and used more various language.